The profitability of momentum strategy in tech stocks. - Tan, Hiap Sing. (2008)
The basic idea of momentum strategy is to purchase stocks that performed will in the past and sell stocks that performed poorly. In this report, we select a set of stock data in US market and compare the excessive return generated by tech portfolio and non-tech portfolio based on momentum strategy. A total of 16 momentum strategies are considered in this report.